The Kalmyk Folklore Corpus: Plots of Household Fairy Tales (Proceedings of Southern Federal University. Philology, 2018)
Irina S. Nadbitova (Elista, Kalmyk Republic, Russian Federation)The Kalmyk Folklore Corpus is a scholarly publication of unique and vivid folklore compositions. Inter alia, it aims to introduce newly discovered records into scientific discourse. Kalmyk fairy tales are noted for their vivid originality, and most complete patterns of the diverse fairy tale genres have been included in the Corpus. Plots of household tales were compared to those of the Comparative Directory of Plots developed for the classification East Slavic fairy tales. The paper concludes that world-wide distributed plots within the considered materials contain some peculiar Kalmyk cultural features that manifest themselves in the structure, characters, poetics, and style.Key words: Kalmyk Folklore Corpus, household fairy tales, tradition, plot, translation, informant, sources.